Risk factors for post-contrast acute kidney injury in patients sequentially administered iodine- and gadolinium-based contrast media on the same visit to the emergency department: a retrospective study - Changshin Kang; Soo Hyun Han; Jung Soo Park; Dae Eun Choi (The Korean Society of Nephrology, 2023)
Background This study compares the incidence of post-contrast acute kidney injury (PC-AKI) in patients who received a single administration of iodine-based contrast medium (ICM) with that in patients who received a sequential administration of ICM and gadolinium-based contrast agents (GBCA) in a single visit to an emergency department (ED) to determine the risk factors for PC-AKI. Methods Patients who received one or more contrast media in the ED from 2016 to 2021 were included in this retrospective study. They were divided into the ICM alone and ICM + GBCA groups, and the incidence of PC-AKI was compared between the groups. The risk factors were assessed using a multivariable analysis after propensity score matching (PSM). Results Overall, 6,318 patients were analyzed, of whom 139 were in the ICM + GBCA group. The incidence of PC-AKI was significantly higher in the ICM + GBCA group than in the ICM alone group (10.9% vs. 27.3%, p < 0.001). In the multivariable analysis, sequential administration was a risk factor for PC-AKI, and single administration was not (adjusted odds ratio [95% confidence interval] in the 1:1, 2:1, and 3:1 PSM cohorts: 2.38 [1.25-4.55], 2.13 [1.26-3.60], and 2.28 [1.39-3.72], respectively). In subgroup analyses of the ICM + GBCA group, osmolality (1.05 [1.01-1.10]) and estimated glomerular filtration rate (eGFR, 0.93 [0.88-0.98]) were associated with PC-AKI. Conclusion Compared with a single administration of ICM alone, sequential administration of ICM and GBCA during a single ED visit might be a risk factor for PC-AKI. Osmolality and eGFR might be associated with PC-AKI after sequential administration.